Study of the Antioxidant Activity of Origanum Majorana in vitro (Latakia University Journal -Medical Sciences Series, 2024)
Herbs are used in popular medicine for their therapeutic effects. Phenolic compounds and Ascorbic acid are natural ingredients which have many supporting effects on health. Phenolic compounds are present in herbs such as Origanum Majorana which is used in many countries for medical purposes in popular and traditional medicine, which make it necessary to study its effects according to popular consumption manner. The aim of this study was to determine the phenolic content and ascorbic acid in aqueous extract of Origanum Majorana prepared according to popular consumption, and to study its antioxidant activity in vitro. The phenolic compounds and Ascorbic acid content were 9.1 ± 0.22 mg (GAE) and 0.024±0.45 in 1 gram of dry Origanum Majorana respectively. The antioxidant activity of Origanum Majorana aqueous extract was higher than BHA (synthetic antioxidant) depending on reducing power assay estimated by absorbance, as well as by ferric reducing antioxidant power (FRAP) estimated by ferrous concentration (p-Value